Color Stability and Surface Roughness of Resin Based Direct and Indirect Restorative Materials - Elif Aybala Oktay; Bilge Ersöz; Numan Aydın; Serpil Karaoğlanoğlu (Ankara University, 2021)
This study investigated discoloration and surface roughness (Ra) in resin-based computer aided design (CAD)/computer aided manufacturing (CAM) blocks and direct and indirect composite resins. Using a Teflon mold, disc shaped specimens (8×2 mm2) were fabricated from direct (Estelite Asteria and GrandioSO) and indirect (Gradia Plus) composite resins, and specimens (12×14×2 mm3) were prepared from composite resin CAD/CAM blocks (Vita Enamic, Brilliant Crios, and Cerasmart) (n=10). A profilometer was used to determine the Ra values of all 60 polished samples. These specimens were thermocycled between 5 and 55°C for 3,000 cycles, and they were immersed in coffee solution (37°C) for 1 and 7 days. A spectrophotometer was used to determine the color change (∆E00) with the CIEDE2000 formula after the specimens were polished. ANOVA TUKEY test was performed to analyze the data. The lowest degree of discoloration among the materials tested was found in Vita Enamic ( lt;0.05), whereas the highest degree of discoloration was found in the Gradia Plus indirect composite ( lt;0.05). Direct composite resins have a higher discoloration potential over resin-based CAD/CAM blocks, whereas they are less prone to discoloration than indirect composite resins.